Phenotypic characterization of Ghanaian P. falciparum clinical isolates reveals a homogenous parasite population - Thiam, Laty G.; Nyarko, Prince B.; Ansah, Felix; Niang, Makhtar; Awandare, Gordon A.; Aniweh, Yaw (Frontiers in Immunology, 2022)
Background Erythrocyte invasion by P. falciparum involves functionally overlapping interactions between the parasite’s ligands and the erythrocyte surface receptors. While some P. falciparum isolates necessarily engage the sialic acid (SA) moieties of the erythrocytes during the invasion, others use ligands whose binding is independent of SA for successful invasion. Deciphering the major pathway used by P. falciparum clinical isolates represent a key step toward developing an efficient blood stage malaria vaccine. Methods We collected a total of 156 malaria-infected samples from Ghanaian children aged 2 to 14 years and used a two-color flow cytometry-based invasion assay to assess the invasion phenotype diversity of Ghanaian P. falciparum clinical isolates. Anti-human CR1 antibodies were used to determine the relative contribution of the PfRh4-CR1 interaction in the parasites invasion phenotype and RT-qPCR was used to assess the expression levels of key invasion-related ligands. Results Our findings show no clear association between demographic or clinical data and existing reports on the malaria transmission intensity. The complete invasion data obtained for 156 isolates, showed the predominance of SA-independent pathways in Ghanaian clinical isolates. Isolates from Hohoe and Navrongo had the highest diversity in invasion profile. Our data also confirmed that the PfRh4-CR1 mediated alternative pathway is important in Ghanaian clinical isolates. Furthermore, the transcript levels of ten invasion-related genes obtained in the study showed little variations in gene expression profiles within and between parasite populations across sites. Conclusion Our data suggest a low level of phenotypic diversity in Ghanaian clinical isolates across areas of varying endemicity and further highlight its importance in the quest for new intervention strategies, such as the investigation of blood-stage vaccine targets, particularly those targeting specific pathways and able to trigger the stimulation of broadly neutralizing invasion antibodies.